الإقتصاد اللغوي في القرآن الكريم دراسة دلالية - غربي بكاي (My University, 2012)
Quran a book of legislation with the provisions and laws governing human life, and outlines the way a book language and about; the words and the vocabulary and structures money do without him one, in which evidence of grammar and rhetoric and argument, and the news and stories of the United immemorial, and their relics and Oukaúahm and their days and an interactive exchange, ... And the medicine, wisdom, proverbs and geometry and algebra, in which the assets of the Trades and names of machinery such as sewing, carpentry, construction, weaving, farming, fishing, navigation and drafting, writing, and buying and selling .... One aspect of miracles in the Download Aziz is included it excelled in the methods of rhetoric statement There are many books that talk about the abundance of the word, and accuracy of meaning, and versatility of his style, and overwhelmed by the varieties and colors of rhetoric and argument, and there is an important aspect of the eloquence of the Qur'an: the economy of language , I did not find who wrote it or summarized by copyright, and in which he stated fraction was sparse in the wombs of mothers wrote rhetoric and interpretation, grammar, and I wanted to forming the Dispersion, and Asper Oguarh and questioned Mkamenh, and explained his concept, and show the manifestations, mechanisms and usefulness. Came subject of research marked by B: "The economy of language in the Koran - Study Guidelines - and the problem posed is: What is the meaning of economy of language? What does it do? Is economize in language or in speech? Is it possible for all the varieties of human economy in the language or is it more individual ? What are the manifestations and mechanisms in the Koran? To answer these questions followed the descriptive and analytical approach; because the subject needs to introduce some terminology and concepts, has traced the statement in the Quran verses of the economy of language as a result of factors audio or morphological or grammatical or rhetorical help of including dispersed in the books of interpretation and rhetoric, and then stood on the evidence of analysis and debate, due to the lack of intake, and the Ur way, and the lack of studies in this subject, you do not intervene adequately analyzed some of the issues, but suffice for what the scholars of language and interpretation for fear of slippage in the book of Allah, in verse, and in the launch of the rule. Required and the nature of the research and article to be in the introduction, preamble and sections, each section contains two chapters, and epilogue, and indexes. Vttrguet in the preface to the concept of communication and basic elements of Kalmrsl and the consignee and a channel of communication and others, and the conditions to be provided in each of these items until the connection is good and clear. Also reported that the tongues may differ in the expression of ideas and meanings; some of which tend to elaborate and detail, some of which prefer the economy to speak, and move away from what is no point in mentioning or not it takes place of the modern. The first chapter devoted to the definition of the term economy of language to the Arabs, old and modern, and his terms are synonymous, ie, when Western scholars of linguistics, and showed its relationship to language, and offered examples of it, and the necessary conditions and controls. Of an asset to the economy of language and economy of speech, which shows from which to speak more and more economical than language; as an individual and social language. And concluded that the economy of language penetrates into the speaker system and includes all levels of voice and the morphological and semantic and grammar. The conversation was in the second quarter for the economy of language-level voice, began when the economy of language and appropriate voice, then the manifestation of harmony voice in the Koran and from which the similarity between letters in words and structures, with a representation of her verses from the Quran stating the reasons for impact and vulnerability among the characters of buildings, then talked about the hamza and undergo to achieve and when you alleviate the grammarians and readers, and showed the mitigation and citizen investigation, citing the words in all that Arab scholars, and some readings. And then touched to a number of aspects of the economy of language in the Koran, including: Tilt and toning and special characters and slurring and Alaqlab and enforced and followed, and the functions shown and Results. Chapter III: talked the economy of language on the semantic level, and was initially shared with the multifunctionality of words and modes of expression, and it carries different connotations are templates ready to build out several buildings, and there are several mechanisms that can be used to diversify the significance, including the suspension, and the rotation formulas morphological, and general words, and dissemination of private or the allocation of the year. Then moved to the language versions and vary in use, and found that there are words frequently parroted and spin on the tongues, and there are words of less use, and began in this movements, and letters and then words, and eventually showed that the reason for this is: lightness and weight and the ease and difficulty, Vaharkat, letters, words and light on the tongue more common than others. The origin to an economy of language in the readings, His mother told him, and showed the benefit of multiple readings, and what emerges from this diversity of multiple meaning of the verse one, and utilized the provisions of jurisprudence, and concluded by Chapter imaging technical in the Qur'an, and presentation of events and facts spokesman reported. Chapter IV grabbed the economy of language-level synthetic, and began to talk in which the role of movements to express to clarify the meaning, and that in a speech as the keys that led locks the closed, and grammatical rules developed by the grammarians are all oriented towards reducing the pronunciation, and away as possible from all is difficult or hard and heavy on the tongue, and if the conflict between the general rules with taste Arab; it is to reverse to the other, then moved to talk about the ratio, and the deletion and its causes and conditions and Jamalith technical and rhetorical, and then touched to the brevity and types: outline short and concise Delete. Conclude the chapter by reference and silence, with an indication of their role in clarifying the meaning and Tglath, and provide the time and effort.